PENGARUH PENGANGGARAN PARTISIPATIF, LOCUS OF CONTROL, DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Yuliana, Rissa; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze and test the participative budgeting, locus of control and organizationcommitment to the managerial performance at PT Lea Sanent. Meanwhile, the sample of this research is theemployees who have been working minimal 1 year in the period of budget preparation and the employee isinvolved in the process of budget preparation which starts from the level of supervisor until the level ofmanager. The data collection technique of this research has been obtained by issuing questionnaires. Thisresearch uses primary data which has been collected by using questionnaires which have been issued to therespondents. This research is quantitative method, meanwhile the analysis technique is done by using multiplelinear regressions analysis. The result of this research shows that the participative budgeting, locus of controland organization commitment have positive influence to the managerial performance at PT Lea Sanent.Keywords: participative budgeting, locus of control, organization commitment, managerial performance.